Wisp : a story of hope - Fraillon, Zana; Baker-Smith, Grahame (Sydney, NSW : Hachette Australia, 2018)
Idris is a child refugee, born into a world of tents and fences. He has known no other life than this. He has no memories of the world outside. Then the Wisp arrives, floating in on the evening breeze. Everyone who holds it finds their memories reawakened, their hopes of freedom reborn. But what about Idris, who has no memories? What will happen when he holds the magical Wisp? Storytelling and imagination have the power to offer hope in this extraordinary picture book from the Amnesty CILIP Honour-winning author of The Bone Sparrow, Zana Fraillon, and Kate Greenaway Medal-winning illustrator Grahame Baker Smith.
For pre-school age.
Keywords: Refugee children -- Juvenile fiction; Hope -- Juvenile fiction; Liberty -- Juvenile fiction; Children's stories; Modern & contemporary fiction; Australian